A pot with burnished decoration from a Roman period well near Dobova - Modrijan, Zvezdana; Novšak, Matjaž (Arheološki vestnik, 2015)
A ceramic pot, an iron saw, and iron hoops from a bucket were found in a Roman well near Dobova. The article primarily focuses on the pot with burnished decoration, whose analogies indicate a relatively wide spatial and chronological framework that enables it to be dated to the 5th century. This pot resulted from the merging of influences between Roman inhabitants and new settlers, which is frequently and extensively documented for the end of the 4th and the beginning of the 5th centuries, especially in the area of the Danubian limes. Due to this intensive transition, the ethnic identification of the users of most of such objects remains questionable, which is also true for those who used the discussed finds.